Acoustic-Assited Osmotic Dehydration of Dried Pumpkin Jam - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2016)
Acoustic drying accelerates the mass transfer rate during dehydration. Osmotic dehydration has recently gained a significant interest. It consists of immersing the material to be dried in a hypertonic solution. Acoustic-assisted osmotic dehydration, have been implemented as an alternative pretreatment associated to drying procedures. This study focused on the synergistic effect of osmotic and acoustic dehydration in the dried pumpkin jam production. Our results revealed that pumpkin slices should be soaked in 40% sugar and then dried by convective drier for 4 hours under assistance of ultrasonic wave at frequency 37 kHz in power 500 W. From this combination, the dried pumpkin jam would be obtained with the safe moisture content and high beta-caroten retention.Keywords: Pumpkin, Acoustic, Osmotic, Drying, Jam, Beta-caroten.